Educamídia: formação de professores da rede básica do município de Quevedos - RS - Costa, Andrieli Silveira Azeredo da (2024)
This study is linked to the Professional Master's Course in Network Educational Technologies, in the Research Line Development of Network Educational Technologies at UFSM – RS. When researching more about the relationship between digital information and communication technologies TDICs and education, we can see that there is a great need for continued training for teachers in the area. Therefore, this work aims to carry out an educational curation of the resources available on the EducaMídia program website, and after implementing media education training for teachers in the basic education network in the municipality of Quevedos-RS. EducaMídia is the Instituto Palavra Aberta program with support from Google.org created to train teachers and educational organizations, in addition to engaging society in the media education process, contributing to 21st century education. The materials made available for training went through the educational curation process on the program's website, which is open licensed, thinking about the context and needs of teachers in the municipality of Quevedos-Rs. This theme was chosen because we understand the importance of preparing students to receive and share information responsibly, in order to avoid conflicts and misinformation. The research is of an applied nature, will have a qualitative approach, in terms of objectives it is classified as descriptive and in relation to the procedure, it is classified as a case study type, after a bibliographical research on the topic, a curation will be carried out using the available resources for teacher training on the EducaMídia program website. With continued training for teachers, we aim to contribute to teaching and learning about media education and the digital world, working on such important issues in our current world, forming ethical and responsible citizens in both the physical and digital worlds.